Physical emission of spatially‐modulated radar. Issue 9 (1st December 2014) - Blunt, Shannon D.; McCormick, Patrick; Higgins, Thomas; Rangaswamy, Muralidhar
Abstract : Leveraging the recent development of a physical implementation of arbitrary polyphase codes as spectrally well‐contained waveforms, the notion of spatial modulation is developed whereby a time‐varying beampattern is incorporated into the physical emission of an individual pulse. This subset of the broad category of MIMO radar is inspired by the operation of fixational eye movement within the human eye to enhance visual acuity and also subsumes the notion of the frequency‐diverse array for application to pulsed radar. From this spatial modulation framework, some specific emission examples are evaluated in terms of resolution and sidelobe levels for the delay and angle domains. The impact of spatial modulation upon spectral content is also considered and possible joint delay‐angle emission design criteria are suggested. Simulation results of selected target arrangements demonstrate the promise of enhanced discrimination and the basis for the development of future cognitive radar capabilities that may mimic salient aspects of the visual cortex.